IMPLEMENTASI MODEL PEMBELAJARAN AWARENESS OF THINKING DALAM PROSES PEMBELAJARAN DI PKBM RUMAH KESADARAN. - Devi, Sri; Maysara, Siska Resti; Darmawan, Dadan; Umronih Y, Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of the Awareness of Thinking learning model in improving learning awareness among learners at PKBM Rumah Kesadaran. This research employed a qualitative approach with a descriptive case study design. The research subjects included learners, tutors, and PKBM administrators. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings show that the Awareness of Thinking model was implemented through reflection, discussion, and evaluation of thinking processes, but its implementation was not yet optimal. Some learners remained passive, lacked confidence, and were not accustomed to independent reflection. The main obstacles included passive learning habits, limited learning time, and insufficient tutor facilitation. Therefore, consistent reflective activities and stronger tutor roles are needed to improve its effectiveness.